Sensing of 2,4,6-trinitrotoluene (TNT) and 2,4-dinitrotoluene (2,4-DNT) in the solid state with photoluminescent RuII and IrIII complexes - Mosca, Lorenzo (2015)
A series of metal–organic chromophores containing RuII or IrIII were studied for the luminometric detection of nitroaromatic compounds, including trinitrotoluene (TNT). These complexes display long-lived, intense photoluminescence in the visible region and are demonstrated to serve as luminescent sensors for nitroaromatics. The solution-based behavior of these photoluminescent molecules has been studied in detail in order to identify the mechanism responsible for metal-to-ligand charge-transfer (MLCT) excited state quenching upon addition of TNT and 2,4-dinitrotoluene (2,4-DNT). A combination of static and dynamic spectroscopic measurements unequivocally confirmed that the quenching was due to a photoinduced electron transfer (PET) process. Ultrafast transient absorption experiments confirmed the formation of the TNT radical anion product following excited state electron transfer from these metal complexes. Reported for the first time, photoluminescence quenching realized through ink-jet printing and solid-state titrations was used for the solid-state detection of TNT; achieving a limit-of-quantitation (LOQ) as low as 5.6 ng cm−2. The combined effect of a long-lived excited state and an energetically favorable driving force for the PET process makes the RuII and IrIII MLCT complexes discussed here particularly appealing for the detection of nitroaromatic volatiles and related high-energy compounds.